2008 IEEE Wireless Communications and Networking Conference 2008
DOI: 10.1109/wcnc.2008.239
|View full text |Cite
|
Sign up to set email alerts
|

Realtime Multi-User Multi-Antenna Downlink Measurements

Abstract: Abstract-In this paper, we present real-time broadband multi-user multi-antenna measurements in typical indoor and outdoor scenarios. For the first time, essential frequency-selective functions of a new medium access control (MAC) layer, namely fair resource assignment to multiple users, spatial mode selection and adaptive modulation, have been implemented in real-time on standard digital signal processing hardware. The new MAC layer is steered over wireless feedback and control channels in a closed loop manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Each user selects the best 100 or 25% of sub-bands, respectively, having the highest cooperation gains compared to uncoordinated transmission. We ignore the competition among users since proportional fair scheduling assigns users frequently their best resources [11].…”
Section: ) Successive Feedback Requestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each user selects the best 100 or 25% of sub-bands, respectively, having the highest cooperation gains compared to uncoordinated transmission. We ignore the competition among users since proportional fair scheduling assigns users frequently their best resources [11].…”
Section: ) Successive Feedback Requestsmentioning
confidence: 99%
“…Nt t=1 0.9 · log 2 (1 + 0.85 · σ t,n,i ) − 0.18 (11) where N is the number of subcarriers, N t the number of transmit antennas and i the channel realization.…”
Section: B Evm-based Sinr Estimationmentioning
confidence: 99%
“…[8] for an initial implementation example. In the MAC processor, packets are classified according to the internet protocol (IP) packet number, destination address and type of service (TOS) fields extracted from the IP header [18].…”
Section: Mac Layer Synchronizationmentioning
confidence: 99%
“…3G Long Term Evolution (3G-LTE). A cellular trial system with 2 transmit and 2 receive antennas in 20 MHz bandwidth has been implemented [7] and tested [8]. Although the basic MIMO technology is quite similar, the numbers of in-and outputs for cooperative base stations and hence the complexity are further increased.…”
Section: Introductionmentioning
confidence: 99%
“…We have implemented the distributed CoMP concept in real time on top of an existing LTE trial system described previously [19][20][21]. Implementation of enabling features such as clock synchronization, synchronous data exchange, cell specific pilots, CSI feedback, cooperative precoding, precoded pilots and initial laboratory trials are reported in [22].…”
Section: Introductionmentioning
confidence: 99%